(untitled) (Journal of Rangpur Medical College, 2026)
Background: Unstable trochanteric fractures are common in adults and require stable fixation to enable early mobilization and reduce morbidity. Proximal femoral nail and proximal femoral locking compression plate are frequently used implants, but direct comparative data from local clinical settings remain limited. Objective: This study compared operative, radiological, and functional outcomes between these two fixation methods. Methods: This cross-sectional analytical study was conducted in the Department of Orthopaedic Surgery, Sylhet M.A.G. Osmani Medical College Hospital, Sylhet from January 2017 to December 2018. Twelve adults with unstable trochanteric fractures were enrolled and allocated equally to nail or plate fixation. After clinical assessment and informed consent, fixation was performed as per group allocation. Patients were followed for 24 weeks, assessing operative variables, mobilization milestones, radiological union, complications, and functional outcome using the Harris Hip Score. Statistical significance was set at p<0.05. Results: Operation time was slightly longer with the nail (137.5 min) than the plate (116.7 min). Incision length was significantly shorter with the nail (11.2 cm vs 17.5 cm). Hospital stay was similar in both groups (3 days). The nail allowed earlier mobilization, with partial weight bearing at 3.3 weeks versus 9 weeks, and full weight bearing at 11 weeks versus 20 weeks in the plate group. Radiological union was identical (20 weeks), with 66.7% in each group uniting by 18 weeks. Complication rates were comparable, including implant failure (1 per group) and varus deformity (2 per group). Limb length discrepancy occurred only in the nail group (33.3%). Functional recovery at 24 weeks was similar, with mean scores of 81.0 (nail) and 83.2 (plate). Conclusion: Both implants were effective, but PFN offered advantages in minimal surgical exposure and earlier mobilization, supporting its preference in most unstable fractures. J Rang Med Col.2026 Mar;11(1): 146-152